(untitled) (Journal of Informatics and Mathematical Sciences, 2012)
In this paper, the authors investigate the generalized Hyers-Ulam stability of Euler-Lagrange type Cubic functional equation align 2af(x+ay)+2f(ax-y) =(a^3+a)[f(x+y)+f(x-y)]+2(a^4-1)f(y)align in fuzzy normed space by direct method and fixed point method, where a is fixed integer with a eq 0, ± 1.